Combination of intense pulsed light and fractional CO2 laser treatments for patients with acne with inflammatory and scarring lesions. (3rd April 2013) - Wang, B.; Wu, Y.; Luo, Y.‐J.; Xu, X.‐G.; Xu, T.‐H.; Chen, J. Z. S.; Gao, X.‐H.; Chen, H.‐D.; Li, Y.‐H.
Summary Background. Various laser and light sources are been used increasingly in cosmetic dermatology. Aim. To evaluate the efficacy and safety of combination intense pulsed light (IPL) and fractional CO2 laser in treating patients with acne with both inflammatory and scarring lesions. Methods. In total, 37 Chinese patients with acne with facial inflammatory and scar lesions were treated. Successive sessions of 4–6 IPL treatments followed by 2 sessions of fractional CO2 laser treatments were applied. Effectiveness was determined by the dermatologist's evaluation, patient self‐assessment, and devices that measure skin colour, sebum secretion and skin hydration. Results. IPL treatments significantly reduced the inflammatory lesion score and the atrophic scar score compared with baseline. Subsequent fractional CO2 laser treatments further decreased the atrophic scar score. Both scores remained low when patients were followed up at 6 months. Around 90% of the patients experienced significant or moderate overall improvement, and almost 80% patients rated their results as 'excellent' or 'good'. The melanin index (MI), erythema index (EI) and skin sebum level all significantly decreased after IPL treatments, and the EI and sebum level were still low when assessed at the 3‐month follow‐up, although the MI had increased again. The adverse effects (AEs) of both treatments were transient and bearable. Conclusions. IPL in combination with fractional CO2 laser was effective in treating patients with acne with both inflammatory lesions and atrophic scars, and the AEs were acceptable.